Transmission of two mode coded channels in one fibre using optical directional couplers as mode selective elements - Schmauß, Bernhard (Optical and Quantum Electronics, 1992)
Mode multiplexing, a method for transmitting two signals along one fibre without time-or wavelength-multiplexing is presented with theoretical and experimental results. It is shown that two mode coded channels can be separated using optical directional couplers with enhanced mode selectivity combined with a simple signal processing uni
lhft_intern.bib::thirty_years_LHFT_292